DETERMINAN KONSERVATISME AKUNTANSI: ANALISIS EMPIRIS TERHADAP PERAN INSENTIF PAJAK, PERTUMBUHAN, LEVERAGE, DAN KURS PADA PERUSAHAAN GO-PUBLIC DI BURSA EFEK INDONESIA - Santiyar, Dewi; Machdar, Nera Marinda (Cahaya Ilmu Bangsa, 2024)
Accounting conservatism is an important principle in financial reporting that emphasizes caution in the decision-making process. This research aims to analyze the determinants of accounting conservatism in go-public companies on the Indonesia Stock Exchange, with a focus on the role of tax incentives, growth, leverage and exchange rates. This research uses a panel regression method by analyzing data on companies listed during the 2018–2022 period. The research results show that tax incentives and leverage have a significant influence on accounting conservatism, while growth and exchange rates do not show a significant influence. The results of this research provide valuable insight for companies in developing policies that support more conservative financial reporting practices. By understanding the factors that influence accounting conservatism, companies can improve the quality of their financial reporting, thereby supporting more reliable and efficient decision making.